The international law on climate change / Benoît Mayer. - Mayer, Benoît (Cambridge University Press, 2018)
Global climate change is a topic of continuously growing interest. As more international treaties come into force, media coverage has increased and many universities are now starting to conduct courses specifically on climate change laws and policies. This textbook provides a survey of the international law on climate change, explaining how significant international agreements have sought to promote compliance with general norms of international law. Benoit Mayer provides an account of the rules agreed upon through lengthy negotiations under the United Nations Framework Convention on Climate Change (UNFCCC) and multiple other forums on mitigation, geoengineering, adaptation, loss and damage, and international support. The International Law on Climate Change is suitable for undergraduate and graduate students studying climate, environmental or international law. It is supported by a suite of online resources, available at www.internationalclimatelaw.com, featuring regularly updated lists of complementary materials, weblinks and regular updates for each chapter.